Gambaran Kondisi Lingkungan Fisik Rumah Pada Kejadian Tuberkulosis Di wilayah Puskesmas Bentiring Kota Bengkulu - wulan kusumawardhani; Aplina Kartika Sari (Poltekkes Kemenkes Bengkulu, 2026)
`Introduction : Tuberculosis (TB) is a communicable disease that remains a public health concern in Indonesia, including in Bengkulu City. TB transmission can be influenced by the physical conditions of the home environment. This study aimed to describe the physical housing conditions in tuberculosis cases within the working area of the Bentiring Public Health Center, Bengkulu City . Method : The research employed a descriptive method with an observational approach. The sample consisted of 5 homes of TB patients selected purposively. Data were collected through direct measurements and observations of variables such as ventilation area, humidity, temperature, lighting, wall conditions, floor conditions, and occupancy density. Results : The results showed that most houses had ventilation (60%), humidity (60%), temperature (60%), lighting (80%), and occupancy density (60%) that did not meet health standards. Meanwhile, all houses (100%) had adequate wall and floor conditions. These findings indicate that although some physical components of the house met the standards, several environmental factors still contribute to a higher risk of TB transmission. Therefore, improving ventilation, lighting, and reducing occupancy density is essential as a preventive effort to reduce TB spread in the household environment Keywords: Hygiene, Sanitation, Canteen, School